Assessing Biodiversity Conditions in Cocoa Agroforests with a Rapid Assessment Method: Outcomes from a Large-Scale Application in Ghana - Sandra Oliveira; Jessica E. Raneri; Stephan F. Weise (Diversity, 2023)
Cocoa fields in West Africa traditionally kept other tree species to provide shade for cocoa trees and obtain food and other products. Measuring other trees is paramount to monitoring environmental conditions in cocoa agroforests, but it has been difficult to apply at a large scale. This study presents the results of a rapid assessment method applied in Ghana, developed to measure non-cocoa tree characteristics based on easily observed parameters using sample surveys and mapping tools. We collected data from over 8700 cocoa farms and evaluated their biodiversity performance based on 6 indicators classified according to recommended thresholds to benefit biodiversity conditions. Our results show that species richness, shade cover, and potential for tree succession have the lowest proportions of fields with the recommended levels, with variations among regions and districts. The methodological procedure allowed us to identify priority areas and indicators falling behind desirable thresholds, which can inform training and management approaches regarding biodiversity-friendly practices in cocoa fields tailored to the needs of the farmers. The analysis procedure was developed with open-access automated routines, allowing for easy updates and replication to other areas, as well as for other commodities, enabling comparisons at different spatial scales and contributing to monitoring biodiversity over time.